2014
DOI: 10.4172/2155-9864.1000216
|View full text |Cite
|
Sign up to set email alerts
|

Descriptive Study on Socio-Demographic and Risk factors Associated with the Oral Cancers, Batticaloa District

Abstract: Objective: Sri Lanka has the highest reported incidence of oral cancer in the world. The aim of the study to investigate the relationship of risk factors with oral cancers. Materials & Methods:596 individuals of Batticaloa district were investigated for this study through intervieweradministrated questionnaire within the time frame for the data collection, applying multi stage cluster sampling technique.Results &Discussion: Out of these 596, 63.42% (Nos. 378) are males. 2% (Nos. 11) of the people interviewed h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 13 publications
1
1
1
Order By: Relevance
“…Regarding education, most oral cancer patients in our study were graduates, with 15.02% being illiterate, a finding consistent with Durgadevi Pancharethinam et al’s study (13). Our results contrasted with another study where half of the patients had no schooling, and one-fourth had only primary education (5)(7). The distribution of oral cancer patients by occupation showed that the majority were clerical and skilled workers, with only 8.15% unemployed, in contrast to Ganesh R et al’s findings, where a greater proportion of patients were unemployed and less skilled (5).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Regarding education, most oral cancer patients in our study were graduates, with 15.02% being illiterate, a finding consistent with Durgadevi Pancharethinam et al’s study (13). Our results contrasted with another study where half of the patients had no schooling, and one-fourth had only primary education (5)(7). The distribution of oral cancer patients by occupation showed that the majority were clerical and skilled workers, with only 8.15% unemployed, in contrast to Ganesh R et al’s findings, where a greater proportion of patients were unemployed and less skilled (5).…”
Section: Discussioncontrasting
confidence: 99%
“…Among males, multiple addictive habits were more common, while females predominantly had the habit of tobacco chewing alone. These findings were similar to other studies (7)(14)(19). The duration of habit revealed that most patients had the habit for more than 10 years, with a significant difference observed (p<0.01).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation